1986
DOI: 10.1002/j.1552-4604.1986.tb02918.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Antiemetic Action of Metoclopramide Against Cisplatin‐Induced Emesis by Transdermal Electrical Nerve Stimulation

Abstract: In a double-blind sequential trial, the influence of transdermal electrical nerve stimulation (TENS) was studied in patients who were treated with total infusions of metoclopramide 3.5 mg/kg to counter the emetic action of cisplatin 60-90 mg/m2. Transdermal electrical nerve stimulation further reduced the emetic episodes in ten of 11 treatment pairs (2 alpha = .10). This effect was blocked by naloxone. More surprisingly, TENS reduced the incidence of extrapyramidal effects of metoclopramide (i.e., akathisia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Studies have shown that TENS may exhibit such effects via augmenting the endorphines, encephalins, or both. This hypothesis has been supported by blocking the antiemetic effect of TENS by naloxone [6][7][8]. Saller et al [8] further proposed endogenous neuropeptides and serotoninergic mechanisms to be involved in the antiemetic effects of TENS because of their impact on gastrointestinal activity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have shown that TENS may exhibit such effects via augmenting the endorphines, encephalins, or both. This hypothesis has been supported by blocking the antiemetic effect of TENS by naloxone [6][7][8]. Saller et al [8] further proposed endogenous neuropeptides and serotoninergic mechanisms to be involved in the antiemetic effects of TENS because of their impact on gastrointestinal activity.…”
Section: Discussionmentioning
confidence: 95%
“…Saller et al [8] used TENS together with metoclopramide in preventing cisplatin-related nausea and vomiting. They applied TENS at a frequency of 100 Hz, with a 10-mA current density.…”
Section: Discussionmentioning
confidence: 99%
“…While acupressure alone produced little benefit in cisplatin-induced emesis, TENS was reported to have a synergistic action with antiemetic drugs such as metoclopramide and ondansetron in the prevention of emesis caused by cytotoxic drugs [12,18,22]. Saller et al [22] observed that TENS enhanced the antiemetic action of metoclopramide against cisplatininduced emesis in 10 of 11 treatment pairs that were studied. Similarly, McMillan et al [12] showed that 75% of the cases obtained some extra benefit from addition of TENS to ondansetron in a series of 16 patients receiving cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation (TENS) has also been shown to enhance the effect of antiemetic drugs, and its effects may be mediated by endogenous opioid peptides. 126 A meta-analysis of 19 randomized trials 127 found equivalent benefit of nonpharmacologic treatment of nausea in postsurgical patients compared to traditional therapy. This benefit was not found in children.…”
Section: Serotonin Antagonistsmentioning
confidence: 99%